ENGLISH REGISTERS IN ALLKPOP NEWS ARTICLES - Irhana, Amalia; Arifin, M Bahri; Ariani, Setya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2017)
This research is intended to describe English registers found in Allkpop news articles. The major problem in this research are to find out the English registers found in Allkpop news articles, to identify word formation process undergone by the English registers found in Allkpop news articles, to identify types of changes in meaning served by the English registers found in Allkpop news articles when compared with their lexical meaning in the dictionary, and to identify language functions served by the English registers found in Allkpop news articles. This research belongs to qualitative research employing descriptive method that was performed by collecting data, classifying, analyzing, and then interpreting the data. As the data, the researcher used English registers found in Allkpop news articles that purposively taken in April, 2016. The results of the analysis are as follows. First, there are a total of 30 units of English registers found in Allkpop news articles posted in April, 2016. These 30 units of English registers of words and phrases are found in 503 news articles posted in April, 2016. Second, almost all of English registers that have undergone morphological process are made of compounding process. Third, all of the English registers have different meaning when they are compared with their lexical meaning in the dictionary. The most dominant type of changes in meaning is widening of meaning in which of the total 30 English registers, 21 are identified have undergone widening of meaning process. Fourth, the most dominant language function based on language functions served by the sentences of the news articles that contain English registers is representational function.Keywords: Allkpop, changes in meaning, language function, register, word formation